The Privatization Experiment in Austria - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 1997)
Austria is a country with a historically strong intervention of government. Specifically a large part of the manufacturing sector and electricity had been nationalized after world war II, combined with public ownership in telecommunication, transport and banking this created one of the largest public sectors in Europe. This articles describes experiments of privatization performed in the last decade ranging from the transfer of ownership, corporatisation, liberalization to activities promoting efficiency and competition within the government. We specifically focus on the institutional framework needed for a successful privatization, stressing the role of a professional privatization agent, who monitors the privatization process.
Keywords: 330; Privatisierung; Österreich